2021
DOI: 10.3389/fimmu.2021.682736
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS-STING Pathway: Novel Perspectives in Liver Diseases

Abstract: Liver diseases represent a major global health burden accounting for approximately 2 million deaths per year worldwide. The liver functions as a primary immune organ that is largely enriched with various innate immune cells, including macrophages, dendritic cells, neutrophils, NK cells, and NKT cells. Activation of these cells orchestrates the innate immune response and initiates liver inflammation in response to the danger signal from pathogens or injured cells and tissues. The cyclic GMP-AMP synthase (cGAS)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 113 publications
0
30
0
2
Order By: Relevance
“…CYP and STING receptors have been selected, as they are commonly associated with both liver pathogenesis and are targeted in drug design and development [ 34 , 35 ]. The molecular interactions of T. polium ’s major compounds with these key receptors, which are targeted in liver therapy, were studied.…”
Section: Discussionmentioning
confidence: 99%
“…CYP and STING receptors have been selected, as they are commonly associated with both liver pathogenesis and are targeted in drug design and development [ 34 , 35 ]. The molecular interactions of T. polium ’s major compounds with these key receptors, which are targeted in liver therapy, were studied.…”
Section: Discussionmentioning
confidence: 99%
“…STING signaling in macrophages has been implicated in anti‐tumor immunity, cellular senescence, and autoimmune and inflammatory diseases (Motwani et al, 2019 ). Endogenous mtDNA released from injured liver parenchymal cells induces STING activation in macrophages, which in turn augments inflammatory liver damage (Xu et al, 2021 ). During liver IR injury, ROS cause oxidative damage to the mitochondria, leading to the release of cytosolic mtDNA from injured hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage‐STING signaling mediated sterile inflammation has been implicated in several liver diseases, such as nonalcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD), and liver cancer (Xu et al, 2021 ). Damage‐associated molecular patterns (DAMPs) from injured liver parenchymal cells induce the activation of macrophages via various types of pattern recognition receptors (PPRs), leading to an inflammatory response and liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Innate immunity is the first line of defense against infection, but its excessive activation can result in tissue injury and host lethality [ 27 , 28 ].STING has previously been shown to regulate inflammation and infection in health and disease [ 20 , 29 ]. At present, only a few articles have reported the role of STING in liver IRI [ 30 , 31 ], and the underlying mechanism remains to be determined. In this study, we found that the activation of STING in liver IRI mainly depends on liver macrophages, and that STING promotes the processing of caspase 1-GSDMD in macrophages to aggravate liver IRI.…”
Section: Discussionmentioning
confidence: 99%